2020
DOI: 10.1186/s40001-020-00464-9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with increased severity of disease in COVID-19 pneumonia: a systematic review and meta-analysis

Abstract: Background Obesity has been widely reported to be associated with the disease progression of coronavirus disease 2019 (COVID-19); however, some studies have reported different findings. We conducted a systematic review and meta-analysis to investigate the association between obesity and poor outcomes in patients with COVID-19 pneumonia. Methods A systematic review and meta-analysis of studies from the PubMed, Embase, and Web of Science databases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
149
2
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 74 publications
7
149
2
9
Order By: Relevance
“…Above increasing the risk of different complications such as DM, liver diseases and cardiovascular diseases, we observed obesity also increases the mortality rate and the demand on intensive care facilities among SARS-COV-2 patients, which augments the findings in a previous systematic review. 34 Henceforth, obesity is one of the potential predictors for the study outcomes. However, the underlying mechanism behind the bad prognosis of obese patients still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Above increasing the risk of different complications such as DM, liver diseases and cardiovascular diseases, we observed obesity also increases the mortality rate and the demand on intensive care facilities among SARS-COV-2 patients, which augments the findings in a previous systematic review. 34 Henceforth, obesity is one of the potential predictors for the study outcomes. However, the underlying mechanism behind the bad prognosis of obese patients still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity are increasingly associated with poor outcomes in COVID-19. In a systematic review and meta-analysis of studies and in a large CDC analysis in the United States population, overweight and/or obesity in COVID-19 were associated with an increased risk of hospital admission, invasive ventilation, and death, especially among patients younger than 60 years-old (29,30). Another study reported an association between body mass index and persisting symptoms after more than 28 days (31).…”
Section: Discussionmentioning
confidence: 99%
“…**Systematic review of 22 studies. 12 † †From New York cohort. 14 ‡ ‡Systematic review of 23 studies.…”
Section: Discussionmentioning
confidence: 99%